(untitled) - Somekh, Bridget (New York, N.Y., 2006)
Bridget Somekh draws on her experience of researching the introduction of ICT into education to look at ICT development over the last twenty years. The book provides a fascinating, in-depth analysis of the nature of learning, ICT pedagogies and the processes of change for teachers, schools and education systems. It covers the key issues relating to the innovation of ICT that have arisen over this period, including: the process of change, educational vision for ICT , teacher motivation and engagement , the phenomenon of ‘fit’ to existing practices, systemic constraints. policy and evaluation of its implementation students’ motivation and engagement the penetration of ICT into the home online learning and the ‘disembodied’ teacher.
Keywords: Educational technology,Information technology; Great Britain,Great Britain